PENGASUHAN ANAK USIA DINI BAGI ORANG TUA PEKERJA - Yuki Widiasari; Desti Pujiati (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2017)
Employment sector is not dominated by men, because women can work and participated in that sector. This condition changes the role’s of a mother. Parenting is not only responsibility of mother but also all of family member, especially grandparents. Parenting’s training has aim to repair parenting’s model so it can restore function of caregiver (parents or the guardians). The caregiver understand how to perform parenting carrying for early childhood, so it will give benefit for the children in the future. At this moment children needs a complex stimulation for supporting their developmental task. Most stimulation is obtained from parenting process as a result of intensive and quality interaction.